Study on water demand and capacity at UMP Gambang campus - Nur Faezah, Harith (2012)
The vision of University Malaysia Pahang is to be a world class university. But, that does not mean a sophisticated place have no problem with the scarcity of water. There are a lot of weaknesses to be covered before turn into a world class university. The water supply and the water demand do not accommodate. The interviews and questionnaire were the.research method in the study area. Some data were also collected from the Department of Development and Asset Management. Interviews weredone towards particular party in study area. The respondent was randomly selected and assumed that, they represent the entire population of the study area. The data then were interpreted using Microsoft Excel. The water supply was the major problem of the occurrence of water shortage. The water capacity at UMP Gambang campus can be accommodated with the water demand required. The water shortage only occurred before 2010.The water supply, capacity and demand are directly proportional.